PENGARUH PEMBERIAN AIR REBUSAN DAUN BELIMBING WULUH (Averrhoa bilimbi L.) TERHADAP JUMLAH LEUKOSIT AYAM BROILER YANG MENGALAMI CEKAMAN PANAS - Arjuna, Deni; Saili, Takdir; Tasse, Andi Murlina (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2019)
The objective of this experiment was to evaluate the effect of starfruit leaves-cooked water addition on total and differential leukocyte number of broiler exposed to heat stress. Sixty four DOCbroilers of SR 707 strain were placed randomly in 16 plots (1 x 1 x 0.6 m each) during 36 days ofexperiment. The plots were designed in order that broiler could be exposed to heat stress. Therewere four treatments of starfruit leaves cooked water concentration applied in this experiment: 0%(v/v) of starfruit leaves cooked-water (T0), 5% (v/v) of starfruit leaves cooked-water (T1), 10% (v/v)of starfruit leaves cooked-water (T2), and 15% (v/v) of starfruit leaves cooked-water (T3). Results of this experiment showed that the addition of starfruit leaves cooked-water had no effect on number oftotal and differential leucocyte of broiler exposed to heat stress. However, the addition of 15% ofstarfruit leaves-cooked water could increase the number of leucocyte, decrease the ratio of heterofillymphociteand has no effect on monocyte and eosinofil number, hence it had potential to be animmunostimulator and immunosupresan. Key words: Starfruit leaves, Broiler, Leucocyte, Heat stress, Immunity.Â